INVITATION TO JOIN A HALF-DAY WORKSHOP ON DISASTER MITIGATION FOR BUILDINGS AND STRUCTURES (DMBS 2016) - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 23 February 2016 The School of Civil Engineering, Universiti Sains Malaysia (USM) in collaboration with Toyohashi University of Technology (TUT) will be organising a halfday workshop on Disaster Mitigation for Buildings and Structures (DMBS 2016).